Heart valve calcification and cardiac hemodynamics. Issue 4 (11th March 2021) - Rossi, Andrea; Barbieri, Andrea; Benfari, Giovanni; Gaibazzi, Nicola; Erlicher, Andrea; Mureddu, Gianfrancesco; Frattini, Silvia; Faden, Giacomo; Manicardi, Marcella; Beraldi, Monica; Agostini, Francesco; Lazzarini, Valentina; et al.
Abstarct: Purpose: Heart valve calcification (VC) is associated with increased cardiovascular risk, but the hemodynamic and functional profile of patients affected by VC has not been fully explored. Methods: The study population was formed by consecutive unselected patients included in seven echocardiographic laboratories in a 2‐week period. A comprehensive echocardiographic examination was performed. VC was defined by the presence of calcification on at least one valve. Results: Population was formed of 1098 patients (mean age 65 ± 15 years; 47% female). VC was present in 31% of the overall population. Compared with subjects without VC, VC patients were older (60 ± 14 vs 75 ± 9; P  < .0001), had more hypertension (40% vs 57%; P  = .0005), diabetes (11% vs 18%; P  = .002), coronary artery disease (22% vs 38%; P  = .04), and chronic kidney disease (4% vs 8%; P  = .007). Furthermore, VC patients had lower ejection fraction (55 ± 14 vs 53 ± 25; P  < .0001), worse diastolic function (E/e' 8.5 ± 4.6 vs 13.0 ± 7.1; P  < .0001) and higher pulmonary artery pressure (29 ± 9 vs 37 ± 12; P  < .0001). The association between VC and EF was not independent of etiology (p for VC 0.13), whereas the association with E/e' and PASP was independent in a full multivariate model ( P  < .0001 and P  = .0002, respectively). Conclusion: Heart valve calcification patients were characterized by a worse functional and hemodynamic profile compared to patients with normal valve. The association between VC and diastolic function and PASP were independent in comprehensive multivariate models.